2013
DOI: 10.3126/jncs.v29i0.9259
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of Medicinal Orchids Growing in Nepal

Abstract: Antibacterial activities of different extracts of epiphytic orchids were tested against 5 species of bacteria and antifungal activities were tested against 3 species of fungi. All orchid extracts showed good bacterial Zone of Inhibition (ZOI) against Staphylococcus aureus. The crude extracts of Pholidota imbricata and Coelogyne cristata were shown highest activity against Vibrio cholerae and Staphylococcus aureus respectively. The MIC and MBC value of the extracts of Pholidota imbricata and Coelogyne cristata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Orchid extracts and their components were shown to exhibit antibacterial activity. In earlier studies, the species of Pholidota, Dendrobium and Coelogyne are shown to exhibit antibacterial activity (Marasini and Joshi, 2012;Sandrasagaran et al, 2014). In this study, Agar well diffusion assay was employed to determine antibacterial activity of extract of orchids selected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Orchid extracts and their components were shown to exhibit antibacterial activity. In earlier studies, the species of Pholidota, Dendrobium and Coelogyne are shown to exhibit antibacterial activity (Marasini and Joshi, 2012;Sandrasagaran et al, 2014). In this study, Agar well diffusion assay was employed to determine antibacterial activity of extract of orchids selected.…”
Section: Discussionmentioning
confidence: 98%
“…Orchids are very sensitive to habitat degradation. Although large population of orchids is confined to their natural habitats, their number is decreasing because of high demand, habitat destruction and indiscriminate collection (Kumar et al, 2007;Jalal and Jayanthi, 2012;Marasini and Joshi, 2012;Pant, 2013;Kiran et al, 2013; Orchid extracts and purified compounds are shown to exhibit several bioactivities such as antimicrobial, antioxidant, anthelmintic, insecticidal, antiviral, analgesic, antipyretic, anti-allergic, wound inflammatory activity ., 2012; Kiran et al, 2013).…”
mentioning
confidence: 99%
“…Nevertheless, these plants have played an important role in ancient cultures medicine [3,4]. The research on orchids´ metabolites has been carried out with several species, resulting in the discovering of molecules with a widely chemical activity range [3,4,5,6,7,8]. In Mexico, orchids have been mainly used within the industries of regional handmade crafting and gastronomy, and in the celebration of religious rites, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics: 3% of these total orchid plant-derived compounds are known (Gutierrez 2010, Qasem andFoy 2001) and there are a very few reports available on phytochemical and biochemical aspects of orchids as a potential source of medicinal property. Recent advances in elucidating the biological properties of orchid species and its potential role in health-care suggest they can be used for treatment of various diseases such as anti-rheumatic, anti-carcinogenic, antivirus, antimicrobials, anticonvulsive, neuroprotective, and hypoglycemic activities (Gutierrez 2010, Yonzone et al 2012Marasini andJoshi 2013, Avasthi et al 2013). Various studies on chemical components of orchids and suggest they possess phytoconstituents like phenols, alkaloids, glycosides, triterpenoids, flavonoids and stilbenoids (Gutierrez 2010, Kalaiarasan et al 2011, Teoh 2016).…”
Section: Introductionmentioning
confidence: 99%